IN HOUSE TRAINING UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MEMBUAT MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN MICROSOFT POWER POINT - Paryanti, Paryanti (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2024)
Creating and utilizing interactive learning media in elementary schools is still rarely done and is considered difficult. Therefore, researchers are making efforts to improve teachers' abilities in creating interactive learning media using Microsoft Powerpoint. This effort involves holding an In House Training (IHT) program. IHT is carried out to guide and train teachers in schools to be able to create their own interactive learning media. This IHT is carried out by providing examples of techniques for creating interactive learning media as well as providing peer tutoring assistance on an ongoing basis until the teacher is truly successful in creating it. The results of implementing the IHT program show that the average teacher's ability to create interactive learning media increased from 27.50 to 78.84. The percentage of teachers who could create interactive media well increased from 0% to 77.78% (7 teachers out of a total of 9 teachers). Based on these data, it can be concluded that IHT can improve teachers' abilities in creating interactive learning media using Microsoft PowerPoint.